Gender Diversity in Senior Positions and Firm Performance : Evidence from Europe - Christiansen, Lone Engbo (IMF Working Papers; Working Paper ;, 2016)
This paper examines the link between gender diversity in senior corporate positions and financial performance of 2 million companies in Europe. We document a positive association between corporate return on assets and the share of women in senior positions and establish two potential channels through which gender diversity may affect firm performance. The positive correlation is more pronounced in, first, sectors where women form a larger share of the labor force (such as the services sector) and, second, where complementarities in skills and critical thinking are in high demand (such as high-tech and knowledge-intensive sectors).